Assessment of the Level of Development of Cashless Transactions in the European Union Countries Between 2019–2023 - Adrian Apanel; Marlena Grzelczak (Finanse i Prawo Finansowe, 2025)
The purpose of the article. The aim of the article is to assess the level of development of cashless payment in the European Union countries between 2019 and 2023. The following research question was formulated – which European Union countries are leading, and which are at the bottom of the ranking in terms of the level of development of cashless payment?